UNRAVELING GORONTALO'S LOCAL WISDOM: THE ESSENCE OF COST ACCOUNTING PRACTICE - Mohamad Anwar Thalib (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research departs from the problem of adopting and implementing modern accounting, which can potentially eliminate local wisdom values from accounting practices. This study aims to find the values of local wisdom behind the practice of education cost accounting by scholarship recipient students. This research uses the Islamic paradigm. The approach used is Islamic ethnomethodology. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. The study results found that students used funds from the government to finance educational needs for one semester. Funds sourced from parents are used by students, one of which is to give alms and help to human beings. The practice of accounting in managing educational expenses is conditional on local wisdom values in the form of trust (ama:nati) and mutual help (huyula). Both of these spirits live on the belief that there are other people's rights behind the sustenance that we have and Allah has arranged the sustenance. The results of this study contribute to the presence of the concept of cost accounting practices by students based on local cultural values